2013
DOI: 10.1210/en.2013-1168
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ Activation Inhibits Growth and Survival of Human Endometriotic Cells by Suppressing Estrogen Biosynthesis and PGE2 Signaling.

Abstract: Endometriosis is a chronic inflammatory disease of reproductive age women leading to chronic pelvic pain and infertility. Current antiestrogen therapies are temporizing measures, and endometriosis often recurs. Potential nonestrogenic or nonsteroidal targets are needed for treating endometriosis. Peroxisome proliferator-activated receptor (PPAR)γ, a nuclear receptor, is activated by thiazolidinediones (TZDs). In experimental endometriosis, TZDs inhibit growth of endometriosis. Clinical data suggest potential u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 53 publications
2
28
0
Order By: Relevance
“…115,116 Moreover, PPARγ is expressed in normal endometrium 117 but is downregulated in ectopic endometrium. 118,119 This appears to mirror what has been reported in liver fibrogenesis: PPARγ is highly expressed in quiescent hepatic stellate cells (HSCs, ie, fibroblasts) but downregulated in activated HSCs. 120,121 PPARγ promotes cellular senescence in fibroblasts, 122 and PPARγ agonists induce apoptosis and cell-cycle arrest in cancer cells.…”
Section: Tp53supporting
confidence: 67%
See 1 more Smart Citation
“…115,116 Moreover, PPARγ is expressed in normal endometrium 117 but is downregulated in ectopic endometrium. 118,119 This appears to mirror what has been reported in liver fibrogenesis: PPARγ is highly expressed in quiescent hepatic stellate cells (HSCs, ie, fibroblasts) but downregulated in activated HSCs. 120,121 PPARγ promotes cellular senescence in fibroblasts, 122 and PPARγ agonists induce apoptosis and cell-cycle arrest in cancer cells.…”
Section: Tp53supporting
confidence: 67%
“…Remarkably, miR‐125b upregulation has been reported in endometriosis . Moreover, PPARγ is expressed in normal endometrium but is downregulated in ectopic endometrium . This appears to mirror what has been reported in liver fibrogenesis: PPARγ is highly expressed in quiescent hepatic stellate cells (HSCs, ie, fibroblasts) but downregulated in activated HSCs .…”
Section: Mutations Of Cancer Driver Genes In Endometriosis and Their supporting
confidence: 54%
“…Ovarian endometriomas express higher levels of aromatase and peroxisome proliferator-activated receptor gamma co-activator 1 alpha (PPARGC1A) than associated ectopic lesions and eutopic endometrium (Suganuma et al 2014). Activation of peroxisome proliferator-activated receptor gamma (PPARG) inhibits the growth and survival of human endometriotic cells by suppressing E2 biosynthesis and prostaglandin E2 (PGE2) signaling (Lebovic et al 2013). The use of AIs for the treatment of endometriosis is becoming more common and is discussed below.…”
Section: Pathogenesis and Progression Of Endometriosismentioning
confidence: 99%
“…Hence, the greater mRNA expression of CPS-I in 1WK compared with 3WK and D corroborate treatment differences in protein intake, as well as PUN concentrations 28 h after supplementation (Ryall et al, 1984;Hayden and Straus, 1995;Takagi et al, 2008). Nevertheless, the similar CPS-I mRNA expression between 3WK and D was unexpected, although others have also reported that enzyme activity can be increased without changes in its expression (Banu et al, 2009;Lebovic et al, 2013). Moreover, mRNA translation into the active enzyme requires time (Clancy and Brown, 2008); hence, one can speculate that CPS-I expression assessed 28 h after supplementation reflected the ureagenesis rate at h 36 after supplementation, when PUN concentrations were similar between 3WK and D, and reduced for both treatments compared with 1WK (Figure 1).…”
Section: Parameters Associated With Protein Intakementioning
confidence: 94%